Statistical inference on cointegration rank in error correction models with stationary covariates. - Seo, Byeongseon (Journal of Econometrics, 1998)
This paper aims to extend the cointegration rank test to error correction models with exogenous stationary covariates. The distribution of the likelihood ratio statistic is a function of the canonical correlations between the equation errors with and without the covariates. The distribution approaches the chi-squared distribution as the stationary covariates lower the canonical correlations. This enables more powerful inference concerning the determination of the cointegration rank. Reprinted by permission of the publisher.